Generation of picosecond pulses using soliton compression in a dual cavity laser - Martin Brunzell; Max Widarsson; Fredrik Laurell; Valdas Pasiskevicius (Scientific Reports)
Abstract In this work, the development of a novel ultra-short laser system is presented, building upon previous research in passive mode-locking using cross-amplitude modulation (XAM). By combining XAM with cascaded second-order nonlinearity mode-locking (CSM) the system produced a stable bright-dark two-color output with picosecond pulses and a repetition rate of 275 MHz with an average output power of 100 mW for an 808 nm pump power of 4 W. The experimental setup involved two Nd: YVO4 lasers operating at 1064 nm and 1342 nm, where the two cavities were interconnected with a dichroic mirror allowing for a shared section where a periodically poled KTiOPO4 (PPKTP) was introduced. In the separate sections, the independently diode-pumped laser crystals were placed. The enhanced intra-cavity intensity achieved through XAM enabled effective pulse compression via CSM. The results demonstrate the system’s ability to generate near-transform-limited pulses as short as 14 ps, offering potential for applications such as medical imaging and LIDAR.